Colour Characteristics of the Forest Soils in the Volga–Kama Forest-Steppe Region - A.A. Valeeva; A.B. Alexandrova; G.F. Koposov (Учёные записки Казанского университета: Серия Естественные науки)
The numerical values of colour characteristics in the structurally differentiated soils of the Republic of Tatarstan have been obtained using the colour space models (RGB, HSB, and L*a*b), which make it possible to objectively describe the colour of soils. It has been shown that the intensity of colour components of the forest soils in Tatarstan changes in the following way: from 97 to 187 for red, from 84 to 177 for green, and from 40 to 158 for blue. The intensity of red and green components in the soil profile increases as moving closer to the parent material. Based on the quantitative determination of colour values in 340 soil samples, the regression equations enabling the conversion of RGB images into the Munsell colour system have been constructed.